A Parametric Study of Fire-Damaged Reinforced Concrete Columns under Lateral Loads - Baghdadi, M.; Dimia, M. S.; Baghdadi, D. (Engineering, Technology & Applied Science Research, 2022)
Columns are the structural members of buildings that ensure structural stability. A fire can severely affect the columns’ structural performance by degrading the properties of their constituent materials, thereby reducing the strength capacity, stiffness, and stability. In seismic zones, the knowledge of the post-fire behavior of these elements is a fundamental requirement for a realistic seismic performance assessment. This study utilized numerical analysis using the parametric fire model of Eurocode-1 to estimate the post-fire axial and lateral performance of reinforced concrete columns. In the first step, the axial load-bearing capacity was evaluated from a parametric study for cantilever columns. In the second step, the lateral load capacity, force-displacement behavior, stiffness, ductility, energy dissipation capacity, and residual displacements were estimated to determine the impact of fire damage on the behavior of columns under lateral loads. The results showed that both the lateral load capacity and the ductility of the reinforced concrete columns decreased significantly due to fire exposure. This also indicated that fire damage decreases the vertical load-bearing capacity, and the reduction in lateral capacity was attributed to the loss of concrete’s compressive strength. The column characteristics that significantly influence the residual response behavior were identified as section size, column height, axial load ratio, and concrete’s compressive strength.